The novels : Not without laughter, and, Tambourines to glory - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Collected works of Langston Hughes, 2001)
Although best known as a poet, Langston Hughes was also the author of two novels that richly evoke the black experience in America. First published in 1930 and 1958, respectively, Not without Laughter and Tambourines to Glory reflect the early and late vision of one of the twentieth century's most distinguished men of letters. In his introduction to this combined edition of both novels, Dolan Hubbard addresses Hughes's growing influence on American letters and reveals how a black aesthetic tradition shaped his art and his imagination. Hughes shows us how the discourse of black America informs and alters our understanding of cultural history and of aesthetic values. In Not without Laughter, he movingly tells the story of a black boy growing into manhood in a small Kansas town during the early twentieth century and his experiences with race, family, school, work, music, and religion. His grandmother, a humble religious woman, struggles to keep her family (living with her are two of her three daughters, one son-in-law, and her grandson) together, on the meager income she earns by taking in washing. Set in Harlem, the center of Hughes's spiritual universe, Tambourines to Glory is an urban folk melodrama based on the black fusion of Christian hymns and spirituals with the blues. This comic novel captures the spirit of newly transplanted southern blacks who bend the alien rhythms of the city to the gospel sound. This volume of The Collected Works of Langston Hughes is a testament to a man whose life and writings have had a profound influence on world literature and is proof that Hughes's immense talent embraced not only poetry, but fiction as well.